2010
DOI: 10.1016/j.cell.2010.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The Palmitoylation Machinery Is a Spatially Organizing System for Peripheral Membrane Proteins

Abstract: Reversible S-palmitoylation of cysteine residues critically controls transient membrane tethering of peripheral membrane proteins. Little is known about how the palmitoylation machinery governs their defined localization and function. We monitored the spatially resolved reaction dynamics and substrate specificity of the core mammalian palmitoylation machinery using semisynthetic substrates. Palmitoylation is detectable only on the Golgi, whereas depalmitoylation occurs everywhere in the cell. The reactions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
454
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 404 publications
(482 citation statements)
references
References 56 publications
21
454
1
6
Order By: Relevance
“…Whereas several studies concluded that particular DHHC(s) palmitoylate defined substrates, 14,16,23,30 it was postulated that any Golgi-resident DHHC can palmitoylate the palmitoylable peripheral membrane proteins. 31 Our results argue for some specificity of DHHC proteins toward their substrate, as only knockdown of DHHC7 really impacts Fas palmitoylation. However, residual Fas palmitoylation is detected upon DHHC7 silencing, which can be attributed to incomplete DHHC7 knockdown or to additional minor contribution from other DHHC proteins that the sensitivity of our assay did not allow to identify.…”
Section: Discussionmentioning
confidence: 72%
“…Whereas several studies concluded that particular DHHC(s) palmitoylate defined substrates, 14,16,23,30 it was postulated that any Golgi-resident DHHC can palmitoylate the palmitoylable peripheral membrane proteins. 31 Our results argue for some specificity of DHHC proteins toward their substrate, as only knockdown of DHHC7 really impacts Fas palmitoylation. However, residual Fas palmitoylation is detected upon DHHC7 silencing, which can be attributed to incomplete DHHC7 knockdown or to additional minor contribution from other DHHC proteins that the sensitivity of our assay did not allow to identify.…”
Section: Discussionmentioning
confidence: 72%
“…We and others have established that the membrane trafficking of N-Ras and H-Ras, which are palmitoylated, differs substantially from that of K-Ras4B, in that N-Ras and H-Ras access the PM through the cytoplasmic surface of the Golgi apparatus, whereas K-Ras4B does not associate with the Golgi (5). The protein palmitoylacyltransferase that modifies N-Ras and H-Ras, DHHC9/GCP16, resides on the Golgi (28), and these Ras isoforms engage in a cycle of palmitoylation/depalmitoylation that takes them to and from the PM (29)(30)(31). At steady state, GFP-N-Ras and GFP-H-Ras can clearly be observed on the Golgi in a variety of cultured cells (5).…”
Section: Discussionmentioning
confidence: 99%
“…Tetrahymena, Toxoplasma, and Plasmodium possess 38, 18, and 12 predicted PATs, respectively. PATs reside in different tissues and sub-cellular localizations and are thought to direct the recruitment of proteins to specific membranes: for example, Vac8 to vacuole membrane in yeast (24), RAS2 in mammalian cell lines to the plasma membrane (25), and TgARO in T. gondii to the rhoptry membrane (26,27). A localization map of PATs in T. gondii and P. berghei was recently established, with two PATs found to localize to the IMC (26,28).…”
mentioning
confidence: 99%